2022
DOI: 10.1002/ccd.30218
|View full text |Cite
|
Sign up to set email alerts
|

Iso‐osmolar versus low‐osmolar contrast media and outcomes after percutaneous coronary intervention: Insights from the VA CART Program

Abstract: Objectives To assess whether contrast media type is associated with outcomes in veterans undergoing percutaneous coronary intervention (PCI). Background There is uncertainty about the impact of iso‐osmolar contrast medium (IOCM) versus low‐osmolar contrast medium (LOCM) on acute kidney injury (AKI) and other major adverse renal or cardiovascular events (MARCE) after PCI. We assessed the association between contrast media type and MARCE in patients who underwent PCI within the Veterans Administration Healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(68 reference statements)
0
2
0
Order By: Relevance
“… 40 , 41 Benefits of LOCM in decreasing CA-AKI compared to IOCM were controversial. Jovin et al 42 performed a study using the Veterans Affairs database and showed no difference in major adverse renal and cardiovascular events between LOCM and IOCM use.…”
Section: Discussionmentioning
confidence: 99%
“… 40 , 41 Benefits of LOCM in decreasing CA-AKI compared to IOCM were controversial. Jovin et al 42 performed a study using the Veterans Affairs database and showed no difference in major adverse renal and cardiovascular events between LOCM and IOCM use.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the journal, Jovin et al 4 studied the effect of iso‐osmolar contrast media (IOCM) and outcomes after percutaneous coronary intervention utilizing data from the VA CART program. The authors identified 92,704 PCI encounters from September 2009 through October 2019 in the VA database.…”
mentioning
confidence: 99%